Efikasi Insektisida Abamektin 18 g/l Terhadap Keragaman Spesies, Kelimpahan Populasi Werengdaun Dan Hasil Panen Pada Tanaman Padi Sawah (Oryza sativa L.) - I GEDE WINDU PUTRA; I WAYAN SUPARTHA; I WAYAN SUSILA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Efficacy of 18 g / l Abamectin Insecticide Against Species Diversity, Population Abundance of leafhoppers and Harvesting on Paddy Paddy Crops (Oryza sativa L.) This research was carried out in Buwit Village, Kediri District, Tabanan Regency, starting in September to November 2017. The research objective was to determine the effect of Abamectin insecticide 18 g/l on species diversity, population abundance and yield. This study used a randomized block design (RBD) with 5 replications and 5 treatments (control, 0.50g / l; 1.00g / l; 1.50g / l; 2.00g / l). The results showed that leaf leafhopper species diversity was low, as evidenced by the Shanon diversity index value was <1.5. The low value of species diversity index is caused by the low number of species in each treatment. Relatively higher variation in control compared to treatment. Abundance The highest population of nymphs and leaf leafhoppers was seen at 49 days after planting as much as 8.57. Components of harvest also show a significant difference between control and treatment.